Acute Hepatitis due to Garcinia Cambogia Extract, an Herbal Weight Loss Supplement. (26th July 2018) - Sharma, Akshay; Akagi, Elisa; Njie, Aji; Goyal, Sachin; Arsene, Camelia; Krishnamoorthy, Geetha; Ehrinpreis, Murray
Abstract : The Drug Induced Liver Injury Network reports dietary supplements as one of the most important causes of drug induced hepatotoxicity, yet millions of people use these supplements without being aware of their potential life-threatening side effects. Garcinia cambogia (GC) extract is an herbal weight loss supplement, reported to cause fulminant hepatic failure. We present a case of a 57-year-old female with no previous history of liver disease, who presented with acute hepatitis due to GC extract taken for weight loss, which resolved after stopping it and got reaggravated on retaking it. Obtaining a history of herbal supplement use is critical in the evaluation of acute hepatitis.